Europe Across Boundaries - Duhaut, Noëmie; Paulmann, Johannes (Jahrbuch für Europäische Geschichte / European History Yearbook, 2022)
The present issue of the European History Yearbook showcases research initially presented at the annual Mainz-Oxford graduate workshop "European History Across Boundaries from the Sixteenth to the Twentieth Century". The essays shed the straightjacket of national history and cross boundaries and borders. They do so by discussing the transcultural, transnational, and transimperial scopes of their research.